Self-assembled nanoflower-like FeSe2/MoSe2 heterojunction anode with enhanced kinetics for superior-performance Na-ion half/full batteries. Issue 12 (7th March 2023) - Li, Shengkai; Zhang, Haiyan; Cao, Yuliang; Zhang, Shangshang; Liu, Zhenjiang; Yang, Changsheng; Wang, Yan; Wan, Baoshan
Abstract : Transition metal selenides are a research hotspot in sodium-ion batteries (SIBs). Abstract : Transition metal selenides are a research hotspot in sodium-ion batteries (SIBs). However, slow kinetics and rapid capacity decay due to volume changes during cycling limit their commercial applications. Heterostructures have the ability to accelerate charge transport and are widely used in energy storage devices due to their abundant active sites and lattice interfaces. A rational design of heterojunction electrode materials with excellent electrochemical performance is essential for SIBs. Herein, a novel anode material heterostructured FeSe2 /MoSe2 (FMSe) nanoflower for SIBs was successfully prepared through a facile co-precipitation and hydrothermal route. The as-prepared FMSe heterojunction exhibits excellent electrochemical performance, including a high invertible capacity (493.7 mA h g −1 after 150 cycles at 0.2 A g −1 ), long-term cycling stability (352.2 mA h g −1 even after 4200 cycles at 5.0 A g −1 ) and competitive rate capability (361.2 mA h g −1 at 20 A g −1 ). By matching with a Na3 V2 (PO4 )3 cathode, it can even exhibit ideal cycling stability (123.5 mA h g −1 at 0.5 A g −1 after 200 cycles). Furthermore, the sodium storage mechanism of the FMSe electrodes was systematically determined by ex situ electrochemical techniques. Theoretical calculation also reveals that the heterostructure on the FMSe interface enhances charge transport and promotes reaction kinetics.